Pantoea agglomerans : a marvelous bacterium of evil and good. Part I. Deleterious effects: Dust-borne endotoxins and allergens – focus on cotton dust - Jacek Dutkiewicz; Barbara Mackiewicz; Marta Kinga Lemieszek; Marcin Golec; Janusz Milanowski (Annals of Agricultural and Environmental Medicine, 2015)
The ubiquitous Gram-negative bacterium Pantoea agglomerans (synonyms: Enterobacter agglomerans , Erwinia herbicola ) is known both as an epiphytic microbe developing on the surface of plants and as an endophytic organism living inside the plants. The bacterium occurs also abundantly in plant and animal products, in the body of arthropods and other animals, in water, soil, dust and air, and occasionally in humans. From the human viewpoint, the role of this organism is ambiguous, both deleterious and beneficial: on one side it causes disorders in people exposed to inhalation of organic dusts and diseases of crops, and on the other side it produces substances effective in the treatment of cancer and other diseases of humans and animals, suppresses the development of various plant pathogens, promotes plant growth, and appears as a potentially efficient biofertilizer and bioremediator. P. agglomerans was identified as a predominant bacterium on cotton plant grown all over the world, usually as an epiphyte, rarely as pathogen. It is particularly numerous on cotton bract after senescence. During processing of cotton in mills, bacteria and their products are released with cotton dust into air and are inhaled by workers, causing respiratory and general disorders, usually defined as byssinosis. The most adverse substance is endotoxin, a heteropolymer macromolecule present in the outermost part of the cell wall, consisting of lipopolysaccharide (LPS) as a major constituent, phospholipids and protein. The numerous experiments carried out in last quarter of XXth century on laboratory animals and human volunteers supported a convincing evidence that the inhaled endotoxin produced by P. agglomerans causes numerous pathologic effects similar to those elicited by cotton dust, such as influx of free lung cells into airways and activation of alveolar macrophages which secrete mediators (prostaglandins, platelet-activating factor, interleukin-1, tumor necrosis factor) that cause accumulation of platelets in pulmonary capillaries initiating an acute and chronic inflammation resulting in endothelial cell damage and extravasation of cells and fluids into the lung interstitium. These changes cause bronchoconstriction, the decrement of lung function expressed as reduction of forced expiratory volume in one second (FEV1) and/or diffusion capacity, increase in the airway hyperreactivity and subjective symptoms such as fever, airway irritation and chest tightness. The conclusions from these experiments, performed mostly 2-3 decades ago, did not loose their actuality until recently as so far no other cotton dust component was identified as a more important work-related hazard than bacterial endotoxin. Though also other microbial and plant constituents are considered as potential causative agents of byssinosis, the endotoxin produced by Pantoea agglomerans and other Gram-negative bacteria present in cotton dust is still regarded as a major cause of this mysterious disease.